Green Synthesis and Characterization of Fe-Ti Mixed Nanoparticles for Enhanced Lead Removal from Aqueous Solutions - Shamika P. W. R. Hewage; Harshica Fernando (Molecules)
Heavy metal contamination in water resources presents a significant environmental and public health challenge, with lead being particularly concerning due to its toxicity and persistence. This study reports the green synthesis of Fe-Ti mixed oxide nanoparticles (NPs) using dextrose as a green source and investigates their effectiveness in lead removal from aqueous solutions. The synthesized NPs were characterized using XRD, FTIR, XPS, SEM-EDS, and BET analysis, revealing an amorphous structure with a high surface area (292.89 m2 g−1) and mesoporous characteristics. XPS analysis confirmed the presence of mixed Fe3+/Fe2+ valence states in a Ti4+-rich framework, creating diverse binding sites for lead adsorption. The material exhibited optimal lead removal at pH 5, with adsorption following pseudo-second-order kinetics (R2 > 0.99) and a Langmuir isotherm model (R2 > 0.98). Maximum adsorption capacity reached 25.10 mg g−1 at 40 °C, showing endothermic behavior. The low point of zero charge (PZC, 0.22) and surface hydroxyl groups enabled efficient lead binding possibly through multiple mechanisms. Dose optimization studies established 6 g L−1 as the optimal adsorbent concentration. The synergistic combination of iron’s affinity for heavy metals and titanium’s structural stability, coupled with environmentally friendly synthesis, resulted in a promising material for sustainable water treatment applications.